Cationic membrane‐active peptides – anticancer and antifungal activity as well as penetration into human skin. Issue 5 (May 2014) - Do, Nhung; Weindl, Günther; Grohmann, Lisa; Salwiczek, Mario; Koksch, Beate; Korting, Hans Christian; Schäfer‐Korting, Monika
Abstract Cationic antimicrobial peptides are ancient natural broad‐spectrum antibiotics, and several compounds also exhibit anticancer activity. However, most applications pertain to bacterial infections, and treatment for skin cancer is less frequently considered. The cytotoxicity of melittin, cecropin A, protegrin‐1 and histatin 5 against squamous skin cancer cell lines and normal human keratinocytes was evaluated and compared to established drugs. The results show that melittin clearly outperforms 5‐fluorouracil regarding antitumor activity. Importantly, combined melittin and 5‐fluorouracil enhanced cytotoxic effects on cancer cells and reduced toxicity on normal keratinocytes. Additionally, minimum inhibitory concentrations indicate that melittin also shows superior activity against clinical and laboratory strains of Candida albicans compared to amphotericin B. To evaluate its potential for topical applications, human skin penetration of melittin was investigated ex vivo and compared to two non‐toxic cell‐penetrating peptides (CPPs), low molecular weight protamine (LMWP) and penetratin. The stratum corneum prevents penetration into viable epidermis over 6 h; however, the peptides gain access to the viable skin after 24 h. Inhibition of digestive enzymes during skin penetration significantly enhances the availability of intact peptide. In conclusion, melittin may represent an innovative agent for non‐melanoma skin cancer and infectious skin diseases. In order to develop a drug candidate, skin absorption and proteolytic digestion by skin enzymes need to be addressed.